Uncovering Cloze Testing Practices in Selected Practice Papers for Primary Schools in Kenya - Maroko, Geoffrey M. (Journal of Applied Linguistics and Language Research, 2016)
Reading comprehension is probably the most prominently tested skill in upper primary classes in Kenya. Most test papers, for instance, comprise a fifteen-item cloze test, a fictional passage and a factual one both of which contribute at least twenty items. While the latter two passages mainly focus on the learner’s ability to identify correct answers from the passage, a cloze test taker is expected to provide words that have been omitted deliberately. Assessment may depend on whether the exercise is objective (i.e. students are given multiple choices to use in a cloze) or subjective (i.e. students fill in a cloze with words that would make a given sentence grammatically correct). Consequently, cloze tests require the ability to understand context and vocabulary in order to identify the correct words or type of words that belong in the deleted parts of a text. However, cloze tests are probably the least understood aspect of language testing in schools. Thus, this paper seeks to address the following issues: What aspects of language are tested in cloze tests and how is this done? How are multiple choice questions constructed? What contextual clues are evident in cloze passages? It is hoped that answers to these and other issues could have implications for testing practices and also the development of essential skills for answering such tests.
Keywords: Cloze test